The clock is ticking on schizophrenia: a study protocol for a translational study integrating phenotypic, genomic, microbiome and biomolecular data to overcome disability - Mercuriali, Giacomo; Lodde, Lorenzo; Paribello, Pasquale; Sapienza, Jacopo; Corona, Alice; Ave, Chiara; Pacini, Delia; Nocera, Daniela; Corrias, Carolina; El Kacemi, Sabrina; D'Incalci, Michele; Frau, Ilaria; et al. (Frontiers in Psychiatry, 2024)
Background Shared biological factors may play a role in both the cognitive deficits and the increased prevalence of metabolic syndrome observed in individuals with Schizophrenia (SCZ). These factors could entail disturbances in tryptophan (Trp) to both melatonin (MLT) and kynurenine (Kyn) metabolic pathways, as well as inflammation and alterations in the gut microbiome composition. Methods The present research project aims to investigate this hypothesis by recruiting 170 SCZ patients from two different recruitment sites, assessing their cognitive functions and screening for the presence of metabolic syndrome. Additionally, we plan to assess the impact of a 3-month cognitive remediation therapy on 30 of these patients. We will analyze clinical data alongside serum biomarkers and gene expression related to the Trp- to MLT and Kyn metabolic pathways, markers of inflammatory and composition of the gut microbiome. The association between Trp-MLT-Kyn levels, expression levels of selected genes, inflammatory markers and clinical phenotypes will be analyses in the context of general linear models. Discussion This project has the potential to identify some typical SCZ symptomatic clusters that will be more stringently associated with variations in the Trp-MLT-Kyn/inflammatory system and with a better response to cognitive remediation therapy. Moreover, in a future perspective, it may highlight a group of patients who may benefit from a pharmacological treatment aiming at reinstating the physiological Trp to MLT and Kyn system. Therefore, it has the potential to move research toward a personalized approach for SCZ management.